2019
DOI: 10.1021/acschembio.9b00605
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Pathway Rerouting in Paraburkholderia rhizoxinica Evolved Long-Overlooked Derivatives of Coenzyme F420

Abstract: Author contributions and conflict of interest Daniel Braga performed research, analyzed data (molecular biology, malachite green assay, mass spectrometry) and contributed to writing the manuscript, Daniel Last performed research and analyzed data (structure elucidation, Fno assay, biogas plant studies), Mahmudul Hasan performed research (CofC/D enzyme assays), Huijuan Guo performed research and analyzed data (structure elucidation), Daniel Leichnitz performed research (chemical synthesis), Zerrin Uzum performe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
66
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(81 citation statements)
references
References 37 publications
8
66
2
1
Order By: Relevance
“…Integrating these findings with other recent literature, it is now clear that the substrate for the initial stage of F 420 tail biosynthesis differs between F 420 -producing organisms (19,24,26). We definitively show here that, in mycobacteria, PEP is the substrate for F 420 biosynthesis, resolving the ambiguity in the literature (24,26).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Integrating these findings with other recent literature, it is now clear that the substrate for the initial stage of F 420 tail biosynthesis differs between F 420 -producing organisms (19,24,26). We definitively show here that, in mycobacteria, PEP is the substrate for F 420 biosynthesis, resolving the ambiguity in the literature (24,26).…”
Section: Discussionsupporting
confidence: 82%
“…The study also showed that CofC from Methanocaldococcus jannaschii utilized PEP rather than 2PL for F 420 biosynthesis (24), leading the authors to conclude that PEP is the general precursor for F 420 biosynthesis in microorganisms. However, these findings contradict previous analysis of CofC activity in M. jannaschii cell lysates (19,21), as well as recent biochemical analysis, which shows that CofC preferentially utilizes 2PL for F 420 biosynthesis (26). In turn, these findings cast doubt on whether PEP is truly the preferred substrate for mycobacterial F 420 biosynthesis and whether DH-F 420 -0 is the physiological intermediate in this pathway.…”
contrasting
confidence: 79%
See 2 more Smart Citations
“…In addition to the engineering considerations that this may impose, it may also be responsible for the biochemical diversity of this step in different microorganisms. In different microbes, the CofC/FbiD-dependent step uses 2-phospholactate [75], 3-phosphoglycerate [76] or phosphoenolpyruvate [59] as a substrate, which may reflect the relative abundance of those metabolites in various bacteria and archaea and the thermodynamic constraints on this step.…”
Section: Cofactor Productionmentioning
confidence: 99%